2017
DOI: 10.1111/jog.13279
|View full text |Cite
|
Sign up to set email alerts
|

Management of pulmonary vasodilator therapy in three pregnancies with pulmonary arterial hypertension

Abstract: Pregnancy with pulmonary arterial hypertension (PAH) has a significantly high risk of maternal death and women with PAH are basically advised to avoid pregnancy. Recently, several reports have described pregnant women with PAH who were treated with pulmonary vasodilators during pregnancy and delivered safely. However, the efficacy of this treatment during pregnancy is still not clear. Here we report on the short-term outcomes of three primiparous women with PAH who were prescribed pulmonary vasodilator therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For patients with stable hemodynamics, routine use of vasodilators and other drugs that can interfere with hemodynamics is not recommended. However, for patients with unstable hemodynamics, addition of pulmonary vasodilators on cumulatively on the existing general treatment regimens can significantly reduce the risk of maternal mortality and adverse pregnancy outcomes ( 14 , 114 ). These vasodilators include calcium channel blockers (CCB) ( 4 , 6 , 115 ), prostaglandins and associated analogs ( 7 , 50 , 51 , 55 , 116 ) and phosphodiesterase inhibitors (PDE-I) ( 117 ), but no endothelin receptor antagonists due to the teratogenic potential ( 118 , 119 ).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with stable hemodynamics, routine use of vasodilators and other drugs that can interfere with hemodynamics is not recommended. However, for patients with unstable hemodynamics, addition of pulmonary vasodilators on cumulatively on the existing general treatment regimens can significantly reduce the risk of maternal mortality and adverse pregnancy outcomes ( 14 , 114 ). These vasodilators include calcium channel blockers (CCB) ( 4 , 6 , 115 ), prostaglandins and associated analogs ( 7 , 50 , 51 , 55 , 116 ) and phosphodiesterase inhibitors (PDE-I) ( 117 ), but no endothelin receptor antagonists due to the teratogenic potential ( 118 , 119 ).…”
Section: Treatmentmentioning
confidence: 99%
“…At present, there is no evidence indicating that inhaled iloprost can cause maternal mortality or congenital fetal anomalies. However, it was indicated that inhalation of iloprost within 24 weeks of gestation and perinatal period can significantly reduce the risk of fetal malformations and mortality ( 55 , 114 , 130 ). It is noteworthy that intravenous epoprostenol should be applied if the disease worsens after inhaling iloprost ( 52 , 114 ).…”
Section: Treatmentmentioning
confidence: 99%
“…In addition, the women with severe PAH delivered earlier (35.4 vs. 31.5 weeks, p <0.005) and had higher rates of small-for-gestational age infants. A case series on short-term outcomes of three women with PAH, who were treated with pulmonary vasodilator therapy during pregnancy showed, that this specific treatment can be used safely over the course of pregnancy and may improve maternal and fetal prognosis [48]. Patients received intravenous prostacyclin and 5-phosphodiesterase inhibitor.…”
Section: Pregnancymentioning
confidence: 99%
“…Patients with severe PAH have worse hemodynamic changes and outcomes compared to those with milder disease [ 7 , 9 , 11 , 14 , 15 , 16 ], and estimates of maternal mortality in severe PAH can be 36% or higher [ 17 , 18 ]. However, a number of single institution reports with limited sample sizes have demonstrated improved maternal outcomes [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], particularly in patients with milder disease [ 27 ], highlighting the value of risk stratification and shared decision making in reproductive planning as well as the evolving nature of this area of study. Several neonatal complications are also well reported in the literature, including small for gestational age infants, preterm birth, and fetal mortality [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…If there are any concerns for poor absorption, such as post-operative ileus, patients can be transitioned from oral to IV formulation of phosphodiesterase-5 inhibitors [ 5 ]. Oral phosphodiesterase-5 inhibitors can also be safely combined with parenteral prostaglandin therapy during pregnancy [ 26 , 84 , 86 ].…”
Section: Introductionmentioning
confidence: 99%